1997
DOI: 10.1073/pnas.94.1.271
|View full text |Cite
|
Sign up to set email alerts
|

Capsule switching of Neisseria meningitidis

Abstract: The different sialic acid (serogroups B, C, Y, and W-135) and nonsialic acid (serogroup A) capsular polysaccharides expressed by Neisseria meningitidis are major virulence factors and are used as epidemiologic markers and vaccine targets. However, the identification of meningococcal isolates with similar genetic markers but expressing different capsular polysaccharides suggests that meningococcal clones can switch the type of capsule they express. We identified, except for capsule, isogenic serogroups B [(␣238… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
306
0
7

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(329 citation statements)
references
References 40 publications
10
306
0
7
Order By: Relevance
“…sing high collagen-binding rates (TLJ11-2, TLJ85-4, TLJ137-4 and TLJ9-1) ( A lack of correlation between serotypes and STs has been demonstrated in many bacterial species, such as Streptococcus pneumoniae, Neisseria meningitidis and Streptococcus agalactiae, and the horizontal transfer of capsular biosynthesis genes related to serotyping is speculated to be the reason (Coffey et al, 1991;Luan et al, 2005;Pettigrew et al, 2006;Swartley et al, 1997). In fact, we also reported the association of one ST with two serotypes in our previous work (Lapirattanakul et al, 2008;Nakano et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…sing high collagen-binding rates (TLJ11-2, TLJ85-4, TLJ137-4 and TLJ9-1) ( A lack of correlation between serotypes and STs has been demonstrated in many bacterial species, such as Streptococcus pneumoniae, Neisseria meningitidis and Streptococcus agalactiae, and the horizontal transfer of capsular biosynthesis genes related to serotyping is speculated to be the reason (Coffey et al, 1991;Luan et al, 2005;Pettigrew et al, 2006;Swartley et al, 1997). In fact, we also reported the association of one ST with two serotypes in our previous work (Lapirattanakul et al, 2008;Nakano et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the UK have observed a 66% reduction in the carriage of serogroup C meningococci in 15-17 year olds 1 year after the introduction of MCC vaccine [27]. Concerns were raised that a change in the prevalence of serogroup C carriage due to the pressure exerted by the MCC vaccine might result in capsule switching from serogroup C to serogroup B. Meningococci can change serogroup while maintaining clonal features, thought to be a result of transformation and horizontal DNA exchange in vivo [28]. Capsule switching may be an important virulence mechanism of meningococci by which virulent strains evade natural or vaccine-induced immunity.…”
Section: Genotypic and Phenotypic Characteristics Of Invasive And Carmentioning
confidence: 99%
“…The capsule (cps) locus consists of a four-gene biosynthesis operon that encodes the production of sialic acid or N-acetylmannosamine and the formation of capsule polymers, whereas the divergently transcribed ctrABCD transport operon encodes proteins responsible for capsule translocation (11)(12)(13). Nearby are two genes, lipA and lipB, proposed to be involved in lipidation of capsule polymers (14).…”
mentioning
confidence: 99%